2017
DOI: 10.1002/rra.3194
|View full text |Cite
|
Sign up to set email alerts
|

Can macroinvertebrate biological traits indicate fine‐grained sediment conditions in streams?

Abstract: Excessive inputs of fine-grained sediment can damage aquatic ecosystems both by degrading communities. We quantified changes in the macroinvertebrate biological trait assemblage from a 8 large number of river reaches spanning a national-scale gradient of increasing agricultural fine 9 sediment delivery and retention, having first factored out variation associated with the natural 10 environmental gradient, with the aim of robustly testing predictions of trait response. We found 11 strong support for two of 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…There have been recent calls for an improved mechanistic understanding of the effects of fine sediment on macroinvertebrates (Wilkes, McKenzie, Murphy, & Chadd, ), with some studies documenting variable responses of benthic invertebrates to sedimentation (Descloux et al., ; Mathers, Rice, & Wood, ; Murphy et al., ). The results from these experiments provide the first direct evidence that the effects of sedimentation vary as a function of sediment characteristics (particle size, heterogeneity and loading) and the body size of fauna.…”
Section: Discussionmentioning
confidence: 99%
“…There have been recent calls for an improved mechanistic understanding of the effects of fine sediment on macroinvertebrates (Wilkes, McKenzie, Murphy, & Chadd, ), with some studies documenting variable responses of benthic invertebrates to sedimentation (Descloux et al., ; Mathers, Rice, & Wood, ; Murphy et al., ). The results from these experiments provide the first direct evidence that the effects of sedimentation vary as a function of sediment characteristics (particle size, heterogeneity and loading) and the body size of fauna.…”
Section: Discussionmentioning
confidence: 99%
“…The consideration of traits should be evaluated with caution as a number of recent studies have reported inconsistent responses of invertebrates to fine sediment deposition (Buendia et al, ; Descloux et al, ; Mathers, Rice, & Wood, ; Murphy et al, ). Traits are unlikely to act in isolation but rather as combinations of traits describing life‐history strategies of varying resistance and resilience to stressors such as fine sediment (Murphy et al, ; Verberk, van Noordwijk, & Hildrew, ). Furthermore, the timing of fine sediment events relative to a taxon's life cycle will play an important role (Mathers, Rice, & Wood, ) as will a taxon's preferred habitat and substrate composition (Wilkes et al, ).…”
Section: Controls On Ecological Responses To Fine Sedimentmentioning
confidence: 99%
“…However, knowledge of aquatic biodiversity and trait responses to organic soil deposition in rivers is lacking when compared to the effects of inorganic sand and silt (Jones et al, 2012;Larsen & Ormerod, 2010b;Mustonen et al, 2016). The use of traits to develop mechanistic understanding of invertebrate community responses to fine sedimentation is growing (Descloux, Datry, & Usseglio-Polatera, 2014;Murphy et al, 2017), but it remains unclear whether trait responses to organic sediments are the same as inorganic sediments. These knowledge gaps prevent peatland managers from understanding the significance of soil erosion in terms of effects on biodiversity responses in nearby aquatic systems.…”
Section: Introductionmentioning
confidence: 99%